2016
DOI: 10.3389/fpsyt.2016.00116
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the Early Stage of Schizophrenia

Abstract: Suicide is a relevant leading cause of death among patients affected by schizophrenia. Even if suicidal ideation may be present in different stages of disease, some differences have been described between the risk of suicide in patients experiencing first episode of psychosis and those with long-term schizophrenia. It is particularly higher during the first year of illness and reaches a steady decline over the following years. Suicidal ideation and attempts may also be common among subjects with subthreshold p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
94
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 93 publications
4
94
3
5
Order By: Relevance
“…However, a history of ever having attempted suicide was not significant, which may be explained by the fact that suicide attempts were common among both suicide cases and controls (58% vs. 44%). The proportion of patients with schizophrenia who ever attempt suicide has been estimated at between 10% and 50% (Pompili et al., ; Ventriglio et al., ). A Finnish psychological autopsy study of all suicides by patients diagnosed with schizophrenia during a one‐year period found that 71% had ever attempted suicide (Heila et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a history of ever having attempted suicide was not significant, which may be explained by the fact that suicide attempts were common among both suicide cases and controls (58% vs. 44%). The proportion of patients with schizophrenia who ever attempt suicide has been estimated at between 10% and 50% (Pompili et al., ; Ventriglio et al., ). A Finnish psychological autopsy study of all suicides by patients diagnosed with schizophrenia during a one‐year period found that 71% had ever attempted suicide (Heila et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, suspiciousness also seems to play an independent role beyond depression in the formation of suicidal ideation through various psychological processes including catastrophizing (Startup, Freeman, & Garety, 2007), threat beliefs (Freeman, Garety, Kuipers, Fowler, & Bebbington, 2002) and negative self-cognitions (Collett, Pugh, Waite, & Freeman, 2016). In UHR individuals, although their experiences of suspiciousness are attenuated in nature, the unfamiliarity and confusedness of newly emerging feelings of suspiciousness appear to further contribute to increasing psychological distress and suicidal ideation (Pyle et al, 2015;Ventriglio et al, 2016). Taken together, our current findings suggest that attenuated positive symptoms of UHR individuals, particularly suspiciousness, may represent a heightened risk for suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of suicide is a continuum stretching from suicidal ideation (ideations, intent and plans) to attempted suicide to completed suicide (Ventriglio et al, 2016). Suicidal ideation is a strong predictor of suicide and the basis of suicide prevention in schizophrenia (Chung et al, 2014).…”
Section: Introductionmentioning
confidence: 99%